Diagnosis of primary antibody and complement deficiencies in young adults after a first invasive bacterial infection. (August 2017) - Sanges, S.; Wallet, F.; Blondiaux, N.; Theis, D.; Vérin, I.; Vachée, A.; Dessein, R.; Faure, K.; Viget, N.; Senneville, E.; Leroy, O.; Maury, F.; et al.
Abstract: Objectives: Screening for primary immunodeficiencies (PIDs) in adults is recommended after two severe bacterial infections. We aimed to evaluate if screening should be performed after the first invasive infection in young adults. Methods: Eligible patients were retrospectively identified using hospital discharge and bacteriology databases in three centres during a 3-year period. Eighteen to 40-year-old patients were included if they had experienced an invasive infection with encapsulated bacteria commonly encountered in PIDs ( Streptococcus pneumoniae (SP), Neisseria meningitidis (NM), Neisseria gonorrhoeae (NG), Haemophilus influenzae (HI), or group A Streptococcus (GAS)). They were excluded in case of general or local predisposing factors. Immunological explorations and PIDs diagnoses were retrieved from medical records. Serum complement and IgG/A/M testings were systematically proposed at the time of study to patients with previously incomplete PID screening. Results: The study population comprised 38 patients. Thirty-six had experienced a first invasive episode and a PID was diagnosed in seven (19%): two cases of common variable immunodeficiency revealed by SP bacteraemia, one case of idiopathic primary hypogammaglobulinaemia, and two cases of complement (C6 and C7) deficiency revealed by NM meningitis, one case of IgG2/IgG4 subclasses deficiency revealed by GAS bacteraemia, and one case of specific polysaccharide antibody deficiency revealed by HI meningitis. Two patients had previously experienced an invasive infection before the study period: in both cases, a complement deficiency was diagnosed after a second NM meningitis and a second NG bacteraemia, respectively. Conclusion: PID screening should be considered after a first unexplained invasive encapsulated-bacterial infection in young adults.